2022
DOI: 10.1038/s41598-022-13147-8
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic bacterial pool decomposes tebuthiuron in soil

Abstract: This study aimed to propose an eco-compatible strategy to mitigate the possible environmental contamination caused by tebuthiuron. Therefore, we screened potential tebuthiuron-degrading microorganisms from conventional (CS) and no-till (NTS) systems producing sugarcane. Then, they were bioprospected for their ability of decomposing the target-molecule at 2.48 mmol g−1 and 4.96 mmol g−1 into CO2 via respirometry. Integrating microbiota from CS and NTS into an advantageously synergistic bacterial pool produced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Native microorganisms from sugarcane's rhizosphere had a synergistic bacterial pool able to produce 90 mg CO 2 day −1 upon the target tebuthiuron at 5 mmol g −1 (Lima et al, 2022). Thus, these authors clearly showed the microbial degradation of tebuthiuron in the rhizosphere soil.…”
Section: Phytoremediation Of 14 C-tebuthiuron In Contaminated Soilmentioning
confidence: 79%
See 1 more Smart Citation
“…Native microorganisms from sugarcane's rhizosphere had a synergistic bacterial pool able to produce 90 mg CO 2 day −1 upon the target tebuthiuron at 5 mmol g −1 (Lima et al, 2022). Thus, these authors clearly showed the microbial degradation of tebuthiuron in the rhizosphere soil.…”
Section: Phytoremediation Of 14 C-tebuthiuron In Contaminated Soilmentioning
confidence: 79%
“…Also, this herbicide has a high persistence in the soil (90% degradation time, DT90 = ~385 and 334 d) (Guimarães et al, 2022). However, bacteria can effectively degrade tebuthiuron in soil (Lima et al, 2022) and seawater (Mercurio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As emerging topics, studies on disruptive solutions for the bioremediation of TBT concentrate on plants ( Ferreira et al, 2021 ) and microorganisms ( Lima et al, 2022 ; Nantes et al, 2022 ). They provide significant knowledge about selecting suitable biotechnological models for treating such a pesticide in agricultural soils.…”
Section: Resultsmentioning
confidence: 99%
“…Then we incubated them in a climatic chamber at 25°C ± 2°C, 60% ± 5%, and 12 h photoperiod. We monitored the growth and development of such a bioindicator of residual toxicity for 5 days ( Lima et al, 2022 ). We quantified its percentage germination by visual counting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation